L-Carnitine in Reproductive Health: A Narrative Review on Its Pharmacological Role in Enhancing Fertility Outcomes - Varsha, M; Sundararajan, Sarumathy (International Journal of Pharmaceutical Investigation, 2026)
L-Carnitine, a naturally occurring quaternary amine, plays a crucial role in mitochondrial fatty acid transport and energy metabolism. This narrative review explores the pharmacological significance of L-Carnitine in reproductive health, with a focus on its potential to enhance fertility outcomes in both males and females. Evidence from clinical and experimental studies highlights L-Carnitine’s ability to improve sperm motility, viability, and DNA integrity by mitigating oxidative stress and enhancing mitochondrial function. In females, L-Carnitine contributes to oocyte maturation, ovarian function, and protection against oxidative damage, thereby supporting overall reproductive potential. Despite promising results, variability in dosing regimens and study designs underscores the need for standardized clinical trials. Nonaetheless, L-Carnitine emerges as a promising adjunct therapy in managing infertility, particularly in conditions such as Oligoasthenoteratozoospermia (OAT) and Polycystic Ovary Syndrome (PCOS). This review concludes that L-Carnitine holds therapeutic potential as a safe and effective agent to improve fertility outcomes, warranting further research to optimize its clinical application.
Keywords: L-Carnitine; Fertility; Reproductive Health; Pharmacology; Sperm Quality; Oocyte Maturation; Oxidative Stress; Infertility